Cement joint sealing material for repairing high-speed rail roadbed slab cracks and preparation method of cement joint sealing material
By combining modified acrylic emulsion with amino-modified liquefied lignin, a cement sealing material that meets the requirements of high-speed railway track slabs was prepared, solving the problems of flexibility and durability of existing materials on high-speed railway track slabs and achieving improved high bonding strength and durability.
Patent Information
- Application Number
- CN202610295293.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-11
- Publication Date
- 2026-05-15
AI Technical Summary
Existing polymer cement repair materials cannot meet the high bonding strength, tensile strength, elongation at break and durability requirements of high-speed railway track slabs, especially when used outdoors, they are not resistant to ultraviolet rays and alkalis.
By combining modified acrylic emulsion with amino-modified liquefied lignin, and through the segmented addition of monomers and the introduction of liquefied lignin, a cement sealant with high flexibility, suitable strength and durability is prepared, which enhances the material's resistance to ultraviolet radiation, oxidation and antibacterial properties.
It achieves the tensile strength and bond strength requirements of repair specifications at a low liquid-to-powder ratio, maintains high elongation at break, and has good outdoor durability, making it suitable for the long-term service environment of high-speed railway track slabs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a cement sealing material for repairing cracks in high-speed railway track slabs and its preparation method. Background Technology
[0002] High-speed railways occupy a very important position in my country's transportation industry. The track slab is a unique structure of high-speed railways. In recent years, with the increasing years of operation of high-speed railways and the combined effects of environmental and other factors, the track slab has begun to show damage, especially surface cracks. These cracks seriously affect the drainage and waterproofing functions of the track slab, as well as its service life and lifespan. Therefore, it is necessary to use sealing materials to repair cracks in the track slab.
[0003] Currently used inorganic repair materials cannot meet the flexibility requirements of track slabs under vibration. Organic repair materials, on the other hand, suffer from high cost and poor durability. Polymer cement composites combine the advantages of both inorganic and organic materials and show promise for use as sealing materials for track slab cracks. However, the bond strength or tensile strength of existing polymer cement repair materials is insufficient to meet the requirements of track slab applications, and they rarely consider the durability requirements such as UV resistance and alkali resistance needed for outdoor applications. High-speed railway track slab sealing materials, because they are used in open-air environments and frequently subjected to dynamic loads, require not only high bond strength and tensile strength, but also high elongation at break, and the durability required for outdoor use.
[0004] Therefore, exploring polymer cement formulations that meet the index requirements of high-speed railway track slab sealing materials has practical application significance and value. Summary of the Invention
[0005] The purpose of this invention is to provide a cement sealing material for repairing cracks in high-speed railway track slabs and its preparation method, so as to improve the above-mentioned problems. To achieve the above objective, the technical solution adopted by this invention is as follows:
[0006] In a first aspect, this application provides a cement sealing material for repairing cracks in high-speed railway track slabs, comprising, by weight parts:
[0007] 450-540 parts cement;
[0008] 300 parts of modified acrylic emulsion;
[0009] Defoamer 0.6-1.2 parts;
[0010] Water-reducing agent: 4.5-5.4 parts;
[0011] 0.8-1.2 parts of amino-modified liquefied lignin;
[0012] The raw materials for preparing the modified acrylate emulsion include composite monomers, functional monomers, and amino-modified liquefied lignin.
[0013] The monomers in the combination comprise, by mass parts: 3.8-4.2 parts of n-butyl acrylate, 3.8-4.2 parts of n-butyl methacrylate, 1.4-1.6 parts of isobutyl acrylate, and 0.4-0.6 parts of styrene;
[0014] The functional monomer includes acrylic acid.
[0015] Secondly, this application also provides a method for preparing a cement sealing material for repairing cracks in high-speed railway track slabs, comprising:
[0016] Dissolve 1 / 2 to 4 / 5 of the formulated amount of composite emulsifier in water, and add buffer solution to obtain the first mixture;
[0017] The first mixture was divided into two parts. One part was added with n-butyl acrylate and n-butyl methacrylate to obtain a first pre-emulsified monomer solution. The other part was added with isobutyl acrylate, acrylic acid and styrene to obtain a second pre-emulsified monomer solution.
[0018] Divide the first pre-emulsified monomer solution into two portions; dissolve the remaining composite emulsifier in water and heat it to 85-90℃ under inert gas conditions; add one portion of the first pre-emulsified monomer solution, the second pre-emulsified monomer solution, and another portion of the first pre-emulsified monomer solution dropwise to the mixture in sequence, while simultaneously adding the initiator solution; keep the mixture warm for 1-2 hours to obtain a matured solution;
[0019] Add oxidant and sodium bisulfite solution dropwise to the aging solution at 70-75℃, then cool to below 40℃ and adjust the pH to 7-8; add amino-modified liquefied lignin and stir for 0.5-1h, then cool to room temperature to obtain modified acrylate emulsion.
[0020] Cement sealing materials were prepared using modified acrylic emulsions.
[0021] Beneficial effects:
[0022] To address the shortcomings of polybutyl acrylate (Pacrylate) such as extremely low strength and tackiness, this invention replaces Pacrylate with a large amount of methacrylate, a small amount of tert-butyl acrylate, and a very small amount of styrene, and adds a very small amount of acrylic monomer. By employing a staged addition of different monomers, it can be combined with cement to prepare a polymer that does not tack, possesses suitable strength and toughness, and exhibits good outdoor durability. The introduction of liquefied lignin into the copolymer emulsion ensures uniform dispersion within the emulsion. Furthermore, the polyphenolic structure of lignin endows it with UV resistance, antioxidant properties, and antibacterial properties. The polar groups such as phenolic hydroxyl groups, alcoholic hydroxyl groups, and aldehyde groups in lignin can form covalent bonds and intermolecular hydrogen bonds between the matrix components, significantly enhancing the composite material's strength and weather resistance. Compared to traditional products, this invention's product can meet the tensile strength and bond strength requirements of repair specifications while retaining a high elongation at break, all while maintaining a relatively low liquid-to-powder ratio.
[0023] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing embodiments of the invention. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below through specific embodiments. Obviously, the embodiments described below are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0025] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0026] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0027] This invention provides a cement sealing material for repairing cracks in high-speed railway track slabs, comprising, by weight:
[0028] 450-540 parts cement;
[0029] 300 parts of modified acrylic emulsion;
[0030] Defoamer 0.6-1.2 parts;
[0031] Water-reducing agent: 4.5-5.4 parts;
[0032] The raw materials for preparing the modified acrylate emulsion include composite monomers, functional monomers, and amino-modified liquefied lignin.
[0033] The monomers in the combination comprise, by mass parts: 3.8-4.2 parts of n-butyl acrylate, 3.8-4.2 parts of n-butyl methacrylate, 1.4-1.6 parts of isobutyl acrylate, and 0.4-0.6 parts of styrene;
[0034] The functional monomer includes acrylic acid.
[0035] Optionally, ordinary Portland cement, PO 42.5R, may be used;
[0036] The modified acrylic emulsion was prepared in-house, with a solid content of 55%.
[0037] The water-reducing agent used is polycarboxylate water-reducing agent with a solid content of 45%;
[0038] The defoamer is a polyether-modified silicone defoamer with a solid content of 70%.
[0039] To address the shortcomings of n-butyl acrylate, such as extremely low strength and tackiness, a polymer was prepared by replacing n-butyl acrylate with a large amount of methacrylate, a small amount of tert-butyl acrylate, and a very small amount of styrene, and adding a very small amount of acrylic monomer. By adding different monomers in stages, a polymer that can be combined with cement to produce a non-tacky product with suitable strength and toughness and good outdoor durability was prepared.
[0040] The reason for choosing a large amount of butyl methacrylate instead of n-butyl acrylate is that methacrylate has a -CH3 group attached to an α-C, which, due to its greater steric hindrance and difficulty in rotation, results in a higher tensile strength, higher tensile strength, lower elongation at break, and better hydrolysis resistance. Furthermore, because it does not contain tertiary hydrogen atoms, it exhibits good lightfastness and weather resistance. Based on this, a small amount of tert-butyl acrylate monomer and a small amount of styrene monomer are further added to participate in the copolymerization to further adjust the hardness and flexibility, ultimately achieving a copolymer that meets the requirements for flexibility and strength. This way, while meeting the requirements for strength and toughness, it also satisfies the requirements for outdoor water resistance, lightfastness, and weather resistance. At the same time, it avoids the need to add excessive amounts of acrylic monomers to the copolymerization, thus preventing a deterioration in water resistance.
[0041] Meanwhile, the monomers n-butyl acrylate, isobutyl acrylate, butyl methacrylate, and styrene have very similar densities and are all hydrophobic, which facilitates blending. Furthermore, the product of the reactivity ratios between any two of these monomers is less than 1, which is beneficial for copolymerizing to prepare polyacrylate emulsions with suitable flexibility and hardness. The addition of carboxylic acid to the raw materials enhances the bonding between the organic and inorganic phases through the combination of carboxylate ions and calcium ions in the cement, thereby improving the compatibility of the emulsion with the cement.
[0042] Liquefied lignin is a product of partial degradation via a hot-pressed water / alcohol system, containing phenolic substances and activated degraded lignin. Introducing this liquefied lignin into a copolymer emulsion allows for uniform dispersion within the emulsion, and the polyphenolic structure of the lignin imparts it with UV resistance, antioxidant properties, and antibacterial effects. In this invention, amine auxiliaries are introduced during the liquefaction process, thereby introducing amino auxochrome groups onto the liquefied lignin to enhance UV absorption performance. The reactivity of amino and epoxy groups also enhances the interfacial bonding of the composite material.
[0043] Example 1:
[0044] A cement sealant for repairing cracks in high-speed railway track slabs, comprising, by weight:
[0045] 450 parts cement;
[0046] 300 parts of modified acrylic emulsion;
[0047] 0.6 parts of defoamer;
[0048] 4.5 parts water-reducing agent;
[0049] The raw materials for preparing the modified acrylic emulsion include, by mass parts:
[0050] 45 units of the combined monomer;
[0051] One functional monomer;
[0052] 1.5 parts of compound emulsifier;
[0053] 0.2 parts initiator;
[0054] 0.2 parts of buffer solution;
[0055] Oxidizing agent 0.04 parts;
[0056] Sodium bisulfite 0.04 parts;
[0057] 45 parts water;
[0058] One part of amino-modified liquefied lignin.
[0059] The monomers in the combination comprise, by mass parts: 4.2 parts of n-butyl acrylate, 4 parts of n-butyl methacrylate, 1.5 parts of isobutyl acrylate, and 0.5 parts of styrene.
[0060] The functional monomer includes acrylic acid;
[0061] The composite emulsifier comprises sodium dodecyl sulfate, an anionic surfactant, and OP-20, a nonionic surfactant with a high cloud point; the mass ratio of the two is 2:1.
[0062] The water-reducing agent is a polycarboxylate water-reducing agent, and the defoamer is a polyether-modified silicone defoamer;
[0063] The method for preparing the cement sealant includes:
[0064] S100, Preparation of amino-modified liquefied lignin:
[0065] S110. Add lignin powder to water at a mass ratio of lignin powder to water of 1:10, then add ethylenediamine (modifier) at a volume of 5% of water to obtain a mixture.
[0066] S120. The mixture is heated to 200°C under stirring, kept at this temperature for 0.5 hours, and then cooled to room temperature to obtain amino-modified liquefied lignin.
[0067] S200, Preparation of modified acrylate emulsion:
[0068] S210. Dissolve 2 / 3 of the formulated amount of composite emulsifier in water, and add sodium bicarbonate buffer solution to obtain the first mixture;
[0069] S220. Divide the first mixture into two parts, add n-butyl acrylate and n-butyl methacrylate to one part to obtain a first pre-emulsified monomer solution; add isobutyl acrylate, acrylic acid and styrene to the other part to obtain a second pre-emulsified monomer solution.
[0070] S230. Divide the first pre-emulsified monomer solution into two equal parts; dissolve the remaining 1 / 3 of the composite emulsifier in water and heat it to 85°C under inert gas conditions; add one part of the first pre-emulsified monomer solution, the second pre-emulsified monomer solution, and another part of the first pre-emulsified monomer solution dropwise to the solution in sequence, while adding the initiator solution dropwise simultaneously during the addition of the three solutions; keep warm for 1 hour to obtain a aging solution;
[0071] S240. Add oxidant and sodium bisulfite solution dropwise to the aging solution at 70℃, then cool to below 40℃ and adjust the pH to 7; add amino-modified liquefied lignin and stir for 0.5h, then cool to room temperature to obtain modified acrylate emulsion.
[0072] S300, Cement sealing material prepared using modified acrylic emulsion:
[0073] Add the defoamer and water-reducing agent to the modified acrylic emulsion and stir (at 800 rpm for 3 min) to obtain the liquid.
[0074] The cement and liquid materials are mixed at 800 rpm for 3 minutes to obtain cement sealing material.
[0075] Example 2:
[0076] A cement sealant for repairing cracks in high-speed railway track slabs, comprising, by weight:
[0077] 540 parts of cement;
[0078] 300 parts of modified acrylic emulsion;
[0079] 1 part defoamer;
[0080] 5 parts water-reducing agent;
[0081] The raw materials for preparing the modified acrylic emulsion include, by mass parts:
[0082] 48 units of the combined monomer;
[0083] 1.5 parts of functional monomer;
[0084] Two parts of compound emulsifier;
[0085] 0.3 parts initiator;
[0086] 0.3 parts of buffer solution;
[0087] Oxidizing agent 0.05 parts;
[0088] Sodium bisulfite 0.05 parts;
[0089] 48 parts water;
[0090] Two parts of amino-modified liquefied lignin.
[0091] The monomers in the combination comprise, by mass parts: 3.8 parts of n-butyl acrylate, 3.8 parts of n-butyl methacrylate, 1.4 parts of isobutyl acrylate, and 0.4 parts of styrene.
[0092] The functional monomer includes acrylic acid;
[0093] The composite emulsifier comprises sodium dodecyl sulfate, an anionic surfactant, and OP-20, a nonionic surfactant with a high cloud point; the mass ratio of the two is 3:1.
[0094] The water-reducing agent is a polycarboxylate water-reducing agent, and the defoamer is a polyether-modified silicone defoamer;
[0095] The method for preparing the cement sealant includes:
[0096] S100, Preparation of amino-modified liquefied lignin:
[0097] S110. Add lignin powder to water, with a mass ratio of lignin powder to water of 1:8, and then add ammonia water (modifier), with the volume of ammonia water being 10% of that of water, to obtain a mixture.
[0098] S120. The mixture is heated to 150°C with stirring, kept at this temperature for 1 hour, and then cooled to room temperature with water to obtain amino-modified liquefied lignin.
[0099] S200, Preparation of modified acrylate emulsion:
[0100] S210. Dissolve 2 / 3 of the formulated amount of composite emulsifier in water, and add sodium bicarbonate buffer solution to obtain the first mixture;
[0101] S220. Divide the first mixture into two parts, add n-butyl acrylate and n-butyl methacrylate to one part to obtain a first pre-emulsified monomer solution; add isobutyl acrylate, acrylic acid and styrene to the other part to obtain a second pre-emulsified monomer solution.
[0102] S230. Divide the first pre-emulsified monomer solution into two equal parts; dissolve the remaining 1 / 3 of the composite emulsifier in water and heat it to 90°C under inert gas conditions; add one part of the first pre-emulsified monomer solution, the second pre-emulsified monomer solution, and another part of the first pre-emulsified monomer solution dropwise to the solution in sequence, while simultaneously adding the initiator solution; keep warm for 2 hours to obtain a matured solution;
[0103] S240. Add oxidant and sodium bisulfite solution dropwise to the aging solution at 75℃, then cool to below 40℃ and adjust pH to 8; add amino-modified liquefied lignin and stir for 1 hour, then cool to room temperature to obtain modified acrylate emulsion.
[0104] S300, Cement sealing material prepared using modified acrylic emulsion:
[0105] Add the defoamer and water-reducing agent to the modified acrylic emulsion and stir (at 800 rpm for 3 min) to obtain the liquid.
[0106] The cement and liquid materials are mixed at 800 rpm for 3 minutes to obtain cement sealing material.
[0107] Example 3:
[0108] A cement sealant for repairing cracks in high-speed railway track slabs, comprising, by weight:
[0109] 500 parts of cement;
[0110] 300 parts of modified acrylic emulsion;
[0111] 0.8 parts of defoamer;
[0112] 5.4 parts of water-reducing agent;
[0113] The raw materials for preparing the modified acrylic emulsion include, by mass parts:
[0114] 50 units of the combined monomer;
[0115] Two functional monomers;
[0116] 1.8 parts of compound emulsifier;
[0117] 0.2 parts initiator;
[0118] 0.4 parts of buffer solution;
[0119] Oxidizing agent 0.07 parts;
[0120] Sodium bisulfite 0.04 parts;
[0121] 45 parts water;
[0122] Four parts of amino-modified liquefied lignin.
[0123] The monomers in the combination comprise, by mass parts: 4.2 parts of n-butyl acrylate, 4 parts of n-butyl methacrylate, 1.5 parts of isobutyl acrylate, and 0.6 parts of styrene.
[0124] The functional monomer includes acrylic acid;
[0125] The composite emulsifier comprises sodium dodecyl sulfate, an anionic surfactant, and OP-20, a nonionic surfactant with a high cloud point; the mass ratio of the two is 1.5:1.
[0126] The water-reducing agent is a polycarboxylate water-reducing agent, and the defoamer is a polyether-modified silicone defoamer;
[0127] The method for preparing the cement sealant includes:
[0128] S100, Preparation of amino-modified liquefied lignin:
[0129] S110. Add lignin powder to water, with a mass ratio of lignin powder to water of 1:12, and then add ammonia water (modifier), with the volume of ammonia water being 8% of the water volume, to obtain a mixture.
[0130] S120. The mixture is heated to 170°C under stirring, kept at this temperature for 0.8 hours, and then cooled to room temperature to obtain amino-modified liquefied lignin.
[0131] S200, Preparation of modified acrylate emulsion:
[0132] S210. Dissolve half of the compound emulsifier in water, and add sodium bicarbonate buffer solution to obtain the first mixture.
[0133] S220. Divide the first mixture into two parts, add n-butyl acrylate and n-butyl methacrylate to one part to obtain a first pre-emulsified monomer solution; add isobutyl acrylate, acrylic acid and styrene to the other part to obtain a second pre-emulsified monomer solution.
[0134] S230. Divide the first pre-emulsified monomer solution into two equal parts; dissolve the remaining 1 / 2 of the composite emulsifier in water and heat it to 88°C under inert gas conditions; add one part of the first pre-emulsified monomer solution, the second pre-emulsified monomer solution, and another part of the first pre-emulsified monomer solution dropwise to the solution in sequence, while adding the initiator solution dropwise at the same time during the addition of the three solutions; keep warm for 1 hour to obtain the aging solution;
[0135] S240. Add oxidant and sodium bisulfite solution dropwise to the aging solution at 72℃, then cool to below 40℃ and adjust the pH to 7.5; add amino-modified liquefied lignin and stir for 1 hour, then cool to room temperature to obtain modified acrylate emulsion.
[0136] S300, Cement sealing material prepared using modified acrylic emulsion:
[0137] Add the defoamer and water-reducing agent to the modified acrylic emulsion and stir (at 800 rpm for 3 min) to obtain the liquid.
[0138] The cement and liquid materials are mixed at 800 rpm for 3 minutes to obtain cement sealing material.
[0139] Example 4:
[0140] A cement sealant for repairing cracks in high-speed railway track slabs, comprising, by weight:
[0141] 500 parts of cement;
[0142] 300 parts of modified acrylic emulsion;
[0143] 0.8 parts of defoamer;
[0144] 5.4 parts of water-reducing agent;
[0145] The raw materials for preparing the modified acrylic emulsion include, by mass parts:
[0146] 50 units of the combined monomer;
[0147] Two functional monomers;
[0148] 1.8 parts of compound emulsifier;
[0149] 0.2 parts initiator;
[0150] 0.4 parts of buffer solution;
[0151] Oxidizing agent 0.07 parts;
[0152] Sodium bisulfite 0.04 parts;
[0153] 45 parts water;
[0154] Four parts of amino-modified liquefied lignin.
[0155] The monomers in the combination comprise, by mass parts: 4.2 parts of n-butyl acrylate, 4 parts of n-butyl methacrylate, 1.5 parts of isobutyl acrylate, and 0.6 parts of styrene.
[0156] The functional monomer includes acrylic acid;
[0157] The composite emulsifier comprises sodium dodecyl sulfate, an anionic surfactant, and OP-20, a nonionic surfactant with a high cloud point; the mass ratio of the two is 1.5:1.
[0158] The water-reducing agent is a polycarboxylate water-reducing agent, and the defoamer is a polyether-modified silicone defoamer;
[0159] The method for preparing the cement sealant includes:
[0160] S100, Preparation of amino-modified liquefied lignin:
[0161] S110. Add lignin powder to water, with a mass ratio of lignin powder to water of 1:12, and then add ammonia water (modifier), with the volume of ammonia water being 8% of the water volume, to obtain a mixture.
[0162] S120. The mixture is heated to 170°C under stirring, kept at this temperature for 0.8 hours, and then cooled to room temperature to obtain amino-modified liquefied lignin.
[0163] S200, Preparation of modified acrylate emulsion:
[0164] S210. Dissolve half of the compound emulsifier in water, and add sodium bicarbonate buffer solution to obtain the first mixture.
[0165] S220. Divide the first mixture into two parts, add n-butyl acrylate and n-butyl methacrylate to one part to obtain a first pre-emulsified monomer solution; add isobutyl acrylate, acrylic acid and styrene to the other part to obtain a second pre-emulsified monomer solution.
[0166] S230. Divide the first pre-emulsified monomer solution into two equal parts; dissolve the remaining 1 / 2 of the composite emulsifier in water and heat it to 88°C under inert gas conditions; add one part of the first pre-emulsified monomer solution, the second pre-emulsified monomer solution, and another part of the first pre-emulsified monomer solution dropwise to the solution in sequence, while adding the initiator solution dropwise at the same time during the addition of the three solutions; keep warm for 1 hour to obtain the aging solution;
[0167] S240. Add oxidant and sodium bisulfite solution dropwise to the aging solution at 72℃, then cool to below 40℃ and adjust the pH to 7.5; add amino-modified liquefied lignin and stir for 1 hour, then cool to room temperature to obtain modified acrylate emulsion.
[0168] S300, Cement sealing material prepared using modified acrylic emulsion:
[0169] Add the defoamer and water-reducing agent to the modified acrylic emulsion and stir (at 800 rpm for 3 min) to obtain the liquid.
[0170] The cement and liquid materials are mixed at 800 rpm for 3 minutes to obtain cement sealing material.
[0171] Example 5:
[0172] A cement sealant for repairing cracks in high-speed railway track slabs, comprising, by weight:
[0173] 520 parts of cement;
[0174] 300 parts of modified acrylic emulsion;
[0175] 0.8 parts of defoamer;
[0176] 4.8 parts of water-reducing agent;
[0177] The raw materials for preparing the modified acrylic emulsion include, by mass parts:
[0178] 46 units of the combined monomer;
[0179] One functional monomer;
[0180] 1.6 parts of compound emulsifier;
[0181] 0.2 parts initiator;
[0182] 0.2 parts of buffer solution;
[0183] Oxidizing agent 0.06 parts;
[0184] Sodium bisulfite 0.06 parts;
[0185] 49 portions of water;
[0186] Three parts of amino-modified liquefied lignin.
[0187] The monomers in the combination comprise, by mass parts: 3.9 parts of n-butyl acrylate, 4.1 parts of n-butyl methacrylate, 1.5 parts of isobutyl acrylate, and 0.5 parts of styrene.
[0188] The functional monomer includes acrylic acid;
[0189] The composite emulsifier comprises sodium dodecyl sulfate, an anionic surfactant, and OP-20, a nonionic surfactant with a high cloud point; the mass ratio of the two is 2.5:1.
[0190] The water-reducing agent is a polycarboxylate water-reducing agent, and the defoamer is a polyether-modified silicone defoamer;
[0191] The method for preparing the cement sealant includes:
[0192] S100, Preparation of amino-modified liquefied lignin:
[0193] S110. Add lignin powder to water at a mass ratio of lignin powder to water of 1:9, then add epoxy-based polyethylene glycol amine (modifier) at a volume of 6% of water to obtain a mixture.
[0194] S120. The mixture is heated to 190°C under stirring, kept at this temperature for 0.5 hours, and then cooled to room temperature to obtain amino-modified liquefied lignin.
[0195] S200, Preparation of modified acrylate emulsion:
[0196] S210. Dissolve 4 / 5 of the formulated amount of composite emulsifier in water, and add sodium bicarbonate buffer solution to obtain the first mixture.
[0197] S220. Divide the first mixture into two parts, add n-butyl acrylate and n-butyl methacrylate to one part to obtain a first pre-emulsified monomer solution; add isobutyl acrylate, acrylic acid and styrene to the other part to obtain a second pre-emulsified monomer solution.
[0198] S230. Divide the first pre-emulsified monomer solution into two equal parts; dissolve the remaining 1 / 5 of the composite emulsifier in water and heat it to 85°C under inert gas conditions; add one part of the first pre-emulsified monomer solution, the second pre-emulsified monomer solution, and another part of the first pre-emulsified monomer solution dropwise to the solution in sequence, while adding the initiator solution dropwise at the same time during the addition of the three solutions; keep warm for 1 hour to obtain the aging solution;
[0199] S240. Add oxidant and sodium bisulfite solution dropwise to the aging solution at 74℃, then cool to below 40℃ and adjust the pH to 7.5; add amino-modified liquefied lignin and stir for 1 hour, then cool to room temperature to obtain modified acrylate emulsion.
[0200] S300, Cement sealing material prepared using modified acrylic emulsion:
[0201] Add the defoamer and water-reducing agent to the modified acrylic emulsion and stir (at 800 rpm for 3 min) to obtain the liquid.
[0202] The cement and liquid materials are mixed at 800 rpm for 3 minutes to obtain cement sealing material.
[0203] Comparative Example 1
[0204] A method for preparing a cement sealing material for repairing cracks in high-speed railway track slabs. The raw materials and preparation steps are basically the same as in Example 5. The difference is that the first pre-emulsified monomer solution is added as an additive. All of the first pre-emulsified monomer solution is added dropwise first, and then the second pre-emulsified monomer solution is added dropwise.
[0205] Comparative Example 2
[0206] A method for preparing a cement sealing material for repairing cracks in high-speed railway track slabs. The raw materials and preparation steps are basically the same as in Example 5, except that the combined monomers include, by mass parts: 4.2 parts of n-butyl acrylate, 4 parts of n-butyl methacrylate, 0.5 parts of isobutyl acrylate, and 0.2 parts of styrene.
[0207] Comparative Example 3
[0208] A method for preparing a cement sealing material for repairing cracks in high-speed railway track slabs is provided. The raw materials and preparation steps are basically the same as in Example 5, except that amino-modified liquefied lignin is replaced with unmodified liquefied lignin.
[0209] The cement sealing materials prepared in the above embodiments and comparative examples were tested, and the results are shown in Table 1.
[0210] Table 1
[0211]
[0212] As can be seen from the test results in Table 1, the change in the order of monomer addition affects the distribution of polymer chain segments, which in turn has a directional impact on the core properties of the material, such as bonding strength, alkali resistance, tensile strength, and elongation at break. Adding isobutyl acrylate, acrylic acid, and styrene monomers in the middle can effectively adjust the hardness and softness, thereby meeting the requirements for flexibility and strength. If they are added last, the mechanical property adjustment effect is poor and it is difficult to form a uniform UV-resistant network. If acrylic acid is added last, the polar carboxyl groups on the surface are prone to photo-oxidative degradation under ultraviolet irradiation, causing surface powdering and cracking.
[0213] Reducing the amount of isobutyl acrylate and styrene added will also have a significant impact on tensile strength and UV resistance.
[0214] If liquefied lignin is not modified, its ultraviolet absorption performance will decrease, and the interfacial bonding force will also decrease, affecting the bonding strength of the material.
[0215] The cement sealing material prepared by this invention can not only overcome the problem of poor flexibility of traditional inorganic sealing materials used for repairing cracks in high-speed railway track slabs, but also solve the problems of poor durability, high pollution, and high cost of organic sealing materials. At the same time, it meets the performance requirements of sealing materials for repairing cracks in high-speed railway track slabs in the standard TG / GW 115-2012 "Maintenance Rules for Ballastless Track Lines of High-Speed Railways", and can withstand the repeated vibration loads of high-speed railway track slabs during long-term service.
[0216] The specific embodiments of the present invention have been described in detail above. However, these embodiments are only for illustrating the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims. Any equivalent substitutions, simple changes, or modifications made to the technical solutions of the present invention within the scope of the inventive concept shall fall within the scope of protection of the present invention.
Claims
1. A cement sealing material for repairing cracks in high-speed railway track slabs, characterized in that, By weight parts: 450-540 parts cement; 300 parts of modified acrylic emulsion; Defoamer 0.6-1.2 parts; Water-reducing agent: 4.5-5.4 parts; The raw materials for preparing the modified acrylate emulsion include composite monomers, functional monomers, and amino-modified liquefied lignin. The monomers in the combination comprise, by mass parts: 3.8-4.2 parts of n-butyl acrylate, 3.8-4.2 parts of n-butyl methacrylate, 1.4-1.6 parts of isobutyl acrylate, and 0.4-0.6 parts of styrene; The functional monomer includes acrylic acid.
2. The cement sealing material for repairing cracks in high-speed railway track slabs according to claim 1, characterized in that, The raw materials for preparing the modified acrylate emulsion also include: a composite emulsifier, a buffer solution, an initiator, an oxidant, sodium bisulfite, and water; The composite emulsifier includes anionic surfactants and nonionic surfactants OP-20.
3. The cement sealing material for repairing cracks in high-speed railway track slabs according to claim 2, characterized in that, The buffer solution is sodium bicarbonate; the mass fractions of each raw material are: Combined monomers: 45-50 parts; 1-2 parts of functional monomer; 1.5-2 parts of compound emulsifier; Initiator 0.2-0.3 parts; 0.2-0.4 parts of buffer solution; Oxidizing agent 0.04-0.07 parts; Sodium bisulfite 0.04-0.07 parts; 45-50 parts water; 1-4 parts of amino-modified liquefied lignin.
4. The cement sealing material for repairing cracks in high-speed railway track slabs according to claim 1, characterized in that, The water-reducing agent includes a polycarboxylate water-reducing agent, and the defoamer includes a polyether-modified silicone defoamer.
5. The cement sealing material for repairing cracks in high-speed railway track slabs according to claim 2, characterized in that, In the composite emulsifier, the mass ratio of anionic surfactant to nonionic surfactant OP-20 is (1.5-3):
1.
6. The method for preparing cement sealing material for repairing cracks in high-speed railway track slabs according to any one of claims 1-5, characterized in that, include: Dissolve 1 / 2 to 4 / 5 of the formulated amount of composite emulsifier in water, and add buffer solution to obtain the first mixture; The first mixture was divided into two parts. One part was added with n-butyl acrylate and n-butyl methacrylate to obtain a first pre-emulsified monomer solution. The other part was added with isobutyl acrylate, acrylic acid and styrene to obtain a second pre-emulsified monomer solution. Divide the first pre-emulsified monomer solution into two portions; dissolve the remaining composite emulsifier in water and heat it to 85-90℃ under inert gas conditions; add one portion of the first pre-emulsified monomer solution, the second pre-emulsified monomer solution, and another portion of the first pre-emulsified monomer solution dropwise to the three portions in sequence, while simultaneously adding the initiator solution during the dropwise addition of the three solutions; Keep warm for 1-2 hours to obtain a aging solution; Add oxidant and sodium bisulfite solution dropwise to the aging solution at 70-75℃, then cool to below 40℃ and adjust the pH to 7-8; add amino-modified liquefied lignin and stir for 0.5-1h, then cool to room temperature to obtain modified acrylate emulsion. Cement sealing materials were prepared using modified acrylic emulsions.
7. The preparation method of the cement sealing material for repairing cracks in high-speed railway track slabs according to claim 6, characterized in that, The method of preparing cement sealing materials using modified acrylic emulsion includes: Defoamer and water-reducing agent are added to the modified acrylic emulsion and stirred to obtain a liquid mixture; Cement and liquid materials are mixed together to obtain cement sealant.
8. The preparation method of the cement sealing material for repairing cracks in high-speed railway track slabs according to claim 6, characterized in that, The preparation method of the amino-modified liquefied lignin includes: Lignin powder is added to water, and then a modifier is added to obtain a mixture; the modifier includes at least one of ammonia, ethylenediamine, or epoxy-based polyethylene glycol amine. The mixture was heated to 150-200℃ with stirring, and the reaction was maintained at this temperature for 0.5-1 hour. Then it was cooled to room temperature with water to obtain amino-modified liquefied lignin.
9. The preparation method of the cement sealing material for repairing cracks in high-speed railway track slabs according to claim 8, characterized in that, When lignin powder is added to water, the mass ratio of lignin powder to water is 1:(8-12).
10. The method for preparing cement sealing material for repairing cracks in high-speed railway track slabs according to claim 8, characterized in that, The volume of the modifier is 5-10% of the volume of water.